2020
DOI: 10.1101/2020.01.22.916130
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

N-3 polyunsaturated fatty acids promote astrocyte differentiation and neurotrophin production independent of cAMP in patient-derived neural stem cells

Abstract: 30Evidence from epidemiological and laboratory studies, as well as randomized placebo-controlled 31 trials, suggests supplementation with n-3 polyunsaturated fatty acids (PUFAs) may be efficacious 32 for treatment of major depressive disorder (MDD). The mechanisms underlying n-3 PUFAs 33 potential therapeutic properties remain unknown. There are suggestions in the literature that glial 34 hypofunction is associated with depressive symptoms and that antidepressants may normalize 35 glial function. In this… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 68 publications
1
3
0
Order By: Relevance
“…Results showed that both the high and the low-dose of ω-3 PUFAs were superior to placebo, and that the efficacy of high-dose ω-3 PUFAs was superior to that of low-dose. In line with these findings, clinical studies within our and other laboratories, again using similar concentrations of ω-3 PUFAs, have showed that diets rich in EPA and DHA provide beneficial anti-inflammatory and anti-depressant effects ( Chang et al., 2019 ; Colombo et al., 1989 ; Luo et al., 2020 ; Rapaport et al., 2016 ; Su et al., 2014 ; Yu et al., 2020 ; Zhou et al., 2019 ). Moreover, we have also previously demonstrated that in vitro treatment of human hippocampal progenitors with EPA and DHA can prevent reduction in neurogenesis caused by IL1β, much like treatment with antidepressants, sertraline and venlafaxine, does ( Borsini et al., 2017 ).…”
Section: Inflammation In Depressionsupporting
confidence: 76%
“…Results showed that both the high and the low-dose of ω-3 PUFAs were superior to placebo, and that the efficacy of high-dose ω-3 PUFAs was superior to that of low-dose. In line with these findings, clinical studies within our and other laboratories, again using similar concentrations of ω-3 PUFAs, have showed that diets rich in EPA and DHA provide beneficial anti-inflammatory and anti-depressant effects ( Chang et al., 2019 ; Colombo et al., 1989 ; Luo et al., 2020 ; Rapaport et al., 2016 ; Su et al., 2014 ; Yu et al., 2020 ; Zhou et al., 2019 ). Moreover, we have also previously demonstrated that in vitro treatment of human hippocampal progenitors with EPA and DHA can prevent reduction in neurogenesis caused by IL1β, much like treatment with antidepressants, sertraline and venlafaxine, does ( Borsini et al., 2017 ).…”
Section: Inflammation In Depressionsupporting
confidence: 76%
“…Nutrition-based therapeutic strategies consisting of the omega-3 polyunsaturated fatty acids (ω-3 PUFAs), eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA) are considered promising therapeutic approaches [4,5]. Indeed, clinical studies within our and other laboratories have showed that diets rich in ω-3 PUFAs, such as EPA and DHA provide beneficial anti-inflammatory and antidepressant effects [6][7][8][9][10][11][12]. Moreover, we have also previously demonstrated that in vitro treatment of human hippocampal progenitors with EPA and DHA can prevent reduction in neurogenesis caused by IL1β, much like treatment with antidepressants, sertraline and venlafaxine, does [13].…”
Section: Introductionmentioning
confidence: 99%
“…This ability of PUFAs to protect neurones from the detrimental effects of inflammation is likely to be relevant for their antidepressant action, at least in the sub-group of patients with major depression characterised by immune dysregulation [6][7][8][9][10][11][12]. In particular, activation of the inflammatory response system in these patients is characterised by an increase in the production of inflammatory cytokines, including interleukin-1beta (IL1β) and IL6 both in the periphery and in the cerebrospinal fluid [1,14].…”
Section: Introductionmentioning
confidence: 99%
“…However, with the development of the live-cell CADDi cAMP reporter (Montana Molecular; Bozeman, USA) the level of cAMP inhibition in primary cultures can be assessed via plate reader in a high throughput manner. Recent work has also shown this method of determining real-time cAMP levels is compatible with primary neural stem cells, indicating it may be used successfully in primary striatal cultures (Yu et al, 2020). This experiment can be further strengthened by utilising the recently released β-arrestin2 CADDi (Montana Molecular).…”
Section: Limitations and Future Directionsmentioning
confidence: 99%